2022
DOI: 10.4103/njcp.njcp_177_20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital game addiction on musculoskeletal system of secondary school children

Abstract: Background: The widespread use of digital devices causes adolescents to spend long periods of time in front of the screen. Aims: This study aimed to analyze the impacts of digital game addiction on the musculoskeletal system of secondary school children in Kayseri. Patients and Methods: A total of 1000 healthy children have been included. A questionnaire, which has been prepared by the researchers and questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…During the study analysis, the participants were school and university students (6 - 25 years old) with either an equal or adjusted male-to-female ratio. Of the included research, two articles were from Brazil 18,19 , two from Portugal 20 ,,21 , two from Thailand 22 , and one study each was from Ethiopia 23 , Jordan 24 , Iran 25 , Shanghai 26 , Kuwait 27 , Turkey 28 , Lebanon 29 , and Taiwan 30 .…”
Section: Resultsmentioning
confidence: 99%
“…During the study analysis, the participants were school and university students (6 - 25 years old) with either an equal or adjusted male-to-female ratio. Of the included research, two articles were from Brazil 18,19 , two from Portugal 20 ,,21 , two from Thailand 22 , and one study each was from Ethiopia 23 , Jordan 24 , Iran 25 , Shanghai 26 , Kuwait 27 , Turkey 28 , Lebanon 29 , and Taiwan 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Gaming addiction can have impacts on mental health and have a correlation with psychological problems such as anxiety, depression, and mental stress. In the study of the correlation between online game addiction and mental health problems among college students in Hong Kong, the experimental results found that the severity of video game addiction is positively correlated with depression, anxiety, stress and psychological distress [8]. It can be speculated that the influence of game addiction on mental health may be due to the fact that game addicts spend most of their time on online games, and they do not communicate with others, also the physical discomfort and emotional problems caused by the long-term excessive use of games will affect the psychological status of addicts.…”
Section: Mental Healthmentioning
confidence: 99%
“…Electronic device usage has become widespread among college students. The majority of them frequently utilize digital devices for a variety of purposes, primarily for online learning activities, assignments, chatting, and Internet surfing [ 2 ].…”
Section: Introductionmentioning
confidence: 99%